Vascular and Nerval Damage After Intraoperative Radiation Therapy of the Liver Hilum in a Large Animal Model. (1st June 2014) - Juntermanns, Benjamin; Grabellus, Florian; Zhang, Hongwei; Radunz, Sonia; Bernheim, Johannes; Fingas, Christian Dominik; Sauerwein, Wolfgang; Paul, Andreas; Kaiser, Gernot Maximilian
ABSTRACT It has been demonstrated that intraoperative radiotherapy is a therapeutic option for patients suffering from perihilar cholangiocarcinoma. Aim of our study was to investigate vascular and nerve damages after irradiation of the liver hilum in a pig model. Twenty-four pigs underwent central bile duct resection followed by biliodigestive anastomosis. Nine pigs underwent this surgical procedure alone (group 1). Ten pigs were treated with additional intraoperative radiation therapy (IORT) of 20Gy to the liver hilum (group 2). And five pigs received operation and IORT with 40Gy to the area of anastomosis (group 3). Six weeks after operation and treatment the animals were sacrificed and histopathological examination was performed. Histology showed no vascular or nerve damage in non-irradiated perihilar tissue. Significant changes of nerve structures occurred, as well as vascular damage in large and even more in small hilar arteries in the irradiated neighboring liver tissue. In detail for small hilar arteries: intima proliferation (p ≤ .0001), endothelial swelling (p ≤ .0001), fibrinoid arterial wall necrosis (p ≤ .0001), and arterial thrombosis (p = .0079) were detected. Venous vessels did not show significant dose dependant cell damage. Overall, 20Gy as a single dose application during operation showed similar damage to vessels and nerves compared to 40Gy. A radiation dosage of 20Gy seems to be sufficient to induce necrosis due to vascular and nerve damage in potential malignant liver tissue with acceptable damage to surrounding tissue. Perineural invaded tumor cells might be diminished due to IORT.